Strategic performance measurement system and organisation capabilities: Using levers of control framework - Mohamed, Rapiah; Wee, Shu Hui; Abdul Rahman, Ibrahim Kamal; Abdul Aziz, Rozainun (World Business Institute, 2008)
The purpose of this paper is to use the levers of control to examine the relationship between strategic performance measurement system and organisational capabilities. The main objective is to examine how strategic performance measurement system influences organisational capabilities. This study proposes that strategic performance measurement system is positively related to organisational capabilities. This paper reports the results of a pilot study of a mail survey. The response came from the top management of 80 Malaysian manufacturing and service firms. The results indicate that beliefs, boundary, diagnostic and interactive control system is positively and significantly correlated with overall organisational capabilities. As for the relationship of levers of control dimension and individual organisational capabilities, the result indicates an overall positive and significant relationship. However, the relationship between diagnostic use and entrepreneurship is not significant.